Alternative ATPase domain interactions in eukaryotic Hsp70 chaperones - Ben-Khoud, Yassin; Chen, Chao-Sheng; Ali, Maruf M. U. (Frontiers in Molecular Biosciences, 2023)
Hsp70 molecular chaperones are essential components for maintaining protein homeostasis within cells. They interact with substrate or client proteins in a well characterised fashion that is regulated by ATP and supported by co-chaperones. In eukaryotes there is a vast array of Hsp70 isoforms that may facilitate adaption to a particular cellular compartment and distinct biological role. Emerging data indicate a novel type of interaction between Hsp70 and client protein that does not fit with the classical Hsp70 ATP regulated substrate mechanism. In this review, we highlight Hsp70 ATPase domain interactions with binding partners from various biological systems that we refer to as Hsp70 ATPase alternative binding proteins or HAAB proteins. We identify common mechanistic features that may define how Hsp70 operates when associating with proteins in this alternative HAAB mode of action.